An Approach to Solar Photovoltaic Systems Simulation Utilizing Builder Block: A Case Study of A 100 MW System - Shahad Safaa Faisal; Emad Talib Hashim (Journal of Engineering)
This paper offers a new design, simulation, and trying out a strategy for the Photovoltaic (PV) gadget producing 100 MW· The work explores how different irradiance and PV temperature tiers have an effect on the output power· To enhance the PV system, the proposed work utilizes the Maximum Power Point Tracking (MPPT) technique with a DC-DC boost converter and a 3-phase tie inverter· These components can improve output voltage and convert it into AC electricity for integration into the application grid· The Block Builder tool is taken into consideration a key factor of this work, which enables accurate simulation of various environmental conditions inclusive of a wide range of solar radiation and PV temperature· Consequently, the electric power generated underneath varying parameters can be exactly assessed· In this work, 4 cases are simulated to assess the performance of the proposed system.. The simulation results show that the proposed design gives varying output powers based on changes in solar radiation and PV temperature, which demonstrates the adaptability of the system. In Case 4, the simulation results indicate that when increasing the solar radiation, the energy starts to increase up to 85 MW when solar radiation equals 1000 W/m², which occurs at 3 seconds.